Speed Comparation Between Two-wheeled Fuel and Electrically Converted Vehicle Using Simulation - Abdussalam, Muhammad Zayyana; Arini, Nu Rhahida; Windarko, Novie Ayub (Jurusan Teknik Elektro Politeknik Negeri Ujung Pandang, 2024)
Revo motorcycle conversion using 2 kW electric motor create slow two-wheeled electric vehicle which only reach 23,3 kph compared to it’s ICE propelled version which could reach 100 kph for equal space on chassis. Faster conversion based on Mio motorcycle using 3 kW BLDC motor resulting 75 kph maximum speed. A novel conversion kit based on Beat motorcycle using equal wattage BLDC motor claimed to be 90 kph which have some mechanism modification. To acquire similar comparison without many mechanism modification, simulation conducted using a pair of equally powered electric motorcycle model compared to it’s ICE motorcycle model. With the same 5.9 kW power rate and 250 kg mass resulting higher motorcycle top speed using ICE propulsion which is 61.959 kph, then the electrically converted motorcycle was 52.840 kph.